2021
DOI: 10.3390/ijerph18115684
|View full text |Cite
|
Sign up to set email alerts
|

Examining Protection Motivation and Network Externality Perspective Regarding the Continued Intention to Use M-Health Apps

Abstract: M-health apps have developed rapidly and are widely accepted, but users’ continued intention to use m-health apps has not been fully explored. This study was designed to obtain a better understanding of users’ continued intention to use m-health apps. We developed a theoretical model by incorporating the protection motivation theory and network externalities and conducted an empirical study of a 368-respondent sample. The results showed that: (1) perceived vulnerability has a direct impact on users’ self-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…This study examined the mediating model using 5000 bootstrap samples, which has been proven to be more accurate than the Sobel test [ 73 , 77 ]. As shown in Table 6 , all indirect effects are significant and the 95% confidence interval for the estimates of the mediation effects excludes 0 [ 27 ]. Thus, the bootstrapping results showed that the mediation effects of e-satisfaction were significant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study examined the mediating model using 5000 bootstrap samples, which has been proven to be more accurate than the Sobel test [ 73 , 77 ]. As shown in Table 6 , all indirect effects are significant and the 95% confidence interval for the estimates of the mediation effects excludes 0 [ 27 ]. Thus, the bootstrapping results showed that the mediation effects of e-satisfaction were significant.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Mohammad et al [ 12 ] found that effort expectancy did not affect behavioral intention and perceived reliability of services quality significantly affects individuals’ intentions to accept mHealth services; Hoque and Sorwar [ 25 ] found that effort expectancy significantly affects users’ behavioral intention. In addition, satisfaction with mobile apps and attitude toward such apps has proved to be a critical factor of influencing the continued intention and behavior of using these apps [ 13 , 26 , 27 ]. For example, one study found that satisfaction has mediation effects on the key factors (perceived usefulness, perceived ease of use, flow experience, and behavioral change techniques) of continued intention to use mHealth apps [ 26 ]; another study revealed that attitude positively influences intention to use mHealth apps from protection motivation and network externality perspectives [ 27 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been proven in different contexts, including telemedicine [ 25 ]. Several researchers have reported that satisfaction positively influences patients’ continuous intentions [ 44 , 48 ], online and face-to-face consultation intention [ 68 ], usage intention [ 59 ], and m-health emergency use [ 25 ]. Satisfaction has also been found to positively affect AI [ 22 ].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Social-enhancement focuses on the desire for ensuring the acceptance and approval of others and advancing one’s social status within SNSs [ 65 ], while response efficacy concerns one’s perception of the effectiveness of continuously implementing certain behaviors to help one’s surrounding environments (e.g., PEBs, green behaviors [ 67 , 68 ]). As scholars [ 65 , 69 ] indicated, in addition to self-enhancement, people get involved in social activities because they aspire to fulfill the need for enriching themselves by means of enhancing their social status (i.e., social-enhancement) on the one hand, and by an effective way to fulfill the important need and execute beneficial behaviors (i.e., response efficacy [ 67 , 70 ]) on the other. Given that social-enhancement and response efficacy have consistently been found to be a crucial role in inspiring people’s favorable tendency to execute various helpful behaviors (e.g., PEBs, knowledge contribution, green consumption) [ 65 , 67 , 68 , 69 , 70 ], it is justified to incorporate these two factors as social-motives in this study.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%